2016
DOI: 10.1097/acm.0000000000000849
|View full text |Cite
|
Sign up to set email alerts
|

Separating Residents’ Inpatient and Outpatient Responsibilities

Abstract: Separating residents' inpatient and outpatient responsibilities may improve patient safety, the learning environment, and resident-patient relationships. Future innovations might focus on improving patient safety and decreasing stress in the outpatient environment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(4 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…We found that opportunities and limitations of the health system have practical implications for resident learning. Seeing the importance of team-based care is contradicted by the inconsistent provider continuity while on other rotations, as described by Bates [32]. Residents in our study recognized that continuity in patient care has many benefits and yet acknowledged how the existing schedule structure during training limits accessibility and ownership, highlighting the tension between striving for ideal patient care while accepting the reality of practice.…”
Section: Discussionmentioning
confidence: 69%
“…We found that opportunities and limitations of the health system have practical implications for resident learning. Seeing the importance of team-based care is contradicted by the inconsistent provider continuity while on other rotations, as described by Bates [32]. Residents in our study recognized that continuity in patient care has many benefits and yet acknowledged how the existing schedule structure during training limits accessibility and ownership, highlighting the tension between striving for ideal patient care while accepting the reality of practice.…”
Section: Discussionmentioning
confidence: 69%
“…Three articles focused on continuity with the introduction of an X þ Y schedule with mixed results. [29][30][31] Several studies focused on resident satisfaction with an overall trend toward improvement in reducing inpatient-outpatient conflict 30,[32][33][34][35] and resident satisfaction with ambulatory education, 30,33,36 but no studies found an increase in the desire to pursue primary care careers. 29,32,36 Only 2 studies evaluated improvement in quality of care in X þ Y schedules with mixed results.…”
Section: Clinic Redesignmentioning
confidence: 99%
“…9 In one internal medicine program, only 16% of residents felt that the program minimized conflict between inpatient and outpatient responsibilities; when these responsibilities were separated so residents do not work in the hospital and in the clinic on the same day, 98% of residents agreed that the conflict was minimized. 63 Resident scheduling in transforming programs follows several general principles: 1. Schedules are made far in advance so that clinics can plan their work.…”
Section: Resident Building Block 1: Resident Schedulingmentioning
confidence: 99%